STRENGTHENING CASH MANAGEMENT THROUGH EFFECTIVE INTERNAL CONTROL SYSTEMS - Mukti Prabowo, Rachmad Gesah; Eni Minarni; Kurniawan, Stefanus Tegar (Universitas Tulungagung, 2024)
This study evaluates the effectiveness of cash management practices in financial institutions by examining their alignment with the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework. Utilizing a qualitative research methodology, the study highlights systematic procedures for account openings, deposits, and withdrawals, ensuring operational transparency, efficiency, and customer satisfaction. The findings emphasize the importance of robust internal controls in mitigating risks, safeguarding assets, and improving process reliability. Key COSO components—control environment, risk assessment, control activities, information and communication, and monitoring—are applied to strengthen cash management systems, reducing fraud and enhancing financial reporting accuracy. This structured approach not only facilitates compliance with regulatory standards but also fosters stakeholder confidence and institutional sustainability. The study concludes with recommendations to optimize cash management practices and address emerging challenges in financial governance.